What do final year medical students in germany know and think about climate change?: the ClimAttitude study - Bugaj, Till Johannes; Heilborn, Marie; Terhoeven, Valentin; Kaisinger, Simon; Nagy, Ede; Friederich, Hans-Christoph; Nikendei, Christoph (Medical education online, 2021)
Climate change (CC) is adversely affecting human health and will become far more dangerous in the future, if no substantial measures are taken. Young people in particular are taking an energetic stand for CC awareness. Some CC experts argue that medical doctors are especially well positioned to inform about the impact of CC on public health, as it is well established that they are among the most trusted members of society. However, medical doctors seem to be unsure of their role in addressing CC. This study aimed to investigate future doctors´, i.e., final year medical students´ (FYMS), attitudes towards CC and their personal role in CC education and health care. A questionnaire was developed to examine (1) the expected consequences of CC for FYMS, (2) their perceived individual responsibility, and their attitudes towards an additional (3) professional responsibility. To examine the climate-questionnaire’s component correlations, we ran a factor analysis using oblique (promax) rotation and conducted a one-way ANOVA with repeated measures to compare the mean scores of the factors. Data are presented as mean ± SD or percentage, as appropriate. n = 65 FYMS (response rate: 87%) were participating and all of them completed the questionnaire. Items of the factor professional responsibility showed the lowest level of agreement (47.2 ± 21.2), while the 2 other factors showed higher levels of agreement (expected consequences (75.6 ± 18.4), individual responsibility (75.1 ± 20.6). Future doctors at Heidelberg University Hospital are well-informed about the expected health consequences of CC. They recognize human contributions to CC and make personal decisions to mitigate the impact. However, the opinion that they have a professional responsibility as physicians to patients or society in regard to CC is weaker. Specific teaching could help to change the way future doctors see their role and responsibility in tackling CC.
Gesehen am 14.05.2021